RETORIKA EKONOMI PRABOWO SUBIANTO: ANALISIS VAN DIJK DAN LITERASI KRITIS - Siti Yulianingsih; Undang Sudana (Universitas Hamzanwadi, 2026)
The casual remark by President Prabowo Subianto regarding the economic resilience of rural communities against dollar fluctuations in Nganjuk may at first appear to be an ordinary spontaneous statement. However, when examined through Teun A. van Dijk’s socio-cognitive Critical Discourse Analysis, the statement actually contains a structured populist rhetorical strategy aimed at shaping mass psychology and reducing economic panic at the grassroots level. This qualitative study explores the linguistic structure of the speech based on media documentation from Kompas.com and DetikNews during the May–June 2026 period, and the findings are formulated as a practical instrument for critical literacy in Indonesian language education. Structurally, the text employs a deductive-populist approach that connects the success of regional diplomacy with the strengthening of domestic food and energy resilience. Through simple sentence construction and strategic meaning grouping, the impact of the global crisis on rural areas is obscured. Cognitively, a relaxed and humorous speaking style is used to build the image of a down-to-earth leader while also reducing economic anxiety. In context, this rhetoric emerged amid the weakening of the rupiah and functioned as a means of easing public panic. Interestingly, this informal political text circulating on social media shows strong potential to be developed into contextual teaching material. Transforming the analytical results into a classroom guide can train students to critically examine causal reasoning behind everyday texts, while also shifting language instruction away from rigid memorization of theories.